Synthesis and characterization of carbon quantum dots by microwave heating method - Nabii, Anita (Graduate School, 2023)
Carbon quantum dots (CQDs) have received considerable attention from researchers in recent years due to their rich features such as optical properties, abundance of functional groups on the surface, high solubility in water, low toxicity, and biocompatibility. In addition, they have applications in various fields such as bio-imaging, drug delivery, and photo-catalysis and they are low-cost and environmentally friendly. In this thesis, carbon dots (CDs) were prepared by using orange juice as a carbon source and thiourea as a doping of nitrogen (N) and sulfur (S) with the microwave-assisted synthesis method, which is a low-cost and extremely useful method. The effect of adding the amount of thiourea was examined. Moreover, CQDs obtained by using citric acid instead of orange juice were compared. Synthesized carbon dots are analyzed by optical spectroscopy techniques (UV-Vis Absorption Spectroscopy, Photoluminescence (PL) Emission Spectroscopy), structural properties (X-Ray Diffraction (XRD), Transition Electron Microscope (TEM)) and in-situ Fourier Transform Infrared Spectroscopy (FTIR). According to the XRD result, the diffraction peak belonging to the carbon (002) is dominant and the interlayer distance value calculated based on this peak is approximately 0.32 nm, which is smaller than the graphite carbon. By analysis of TEM images, the particle size was determined to be in the range of 30-50 nm. The results obtained from the FTIR spectra show that N and S-doped CQDs contain various functional groups such as C=C, C=O, C-O-C -CS, -CH, C≡N, -NH, and –OH. The fluorescence quantum yield (QY) of CQDs obtained from orange juice, which was doped with thiourea was calculated according to the quinine sulfate standard. It was observed that the QY values increased by the increase of the amount of thiourea. However, there are limited studies on microwave-assisted synthesis methods, so we preferred to synthesize CQDs by this method, and the value of the highest QY was found approximately 7.1%. Photoluminescence (PL) emission properties depending on the excitation wavelength were examined in different solvent environments such as polar protic (water, methanol, ethanol), aprotic (acetonitrile, acetone), and non-polar (chloroform, n-hexane) in order to consider the effect of solvent polarities. We observed the emission wavelength due to excitation in all solvents towards red-shifted and these shift values changed according to the polarity of the solvents used. However, the PL emission intensity decreases with increasing solvent polarity when the excitation wavelength is greater than 325 nm. On the other hand, the observed PL emission intensity increased with the active role of functional groups in the core of CDs at excitation wavelengths lower than 325 nm excitation.
Mikrodalga ısıtma yöntemiyle karbon kuantum noktalarının sentezi ve karakterizasyonu
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: Carbon quantum dots; (CQDs; carbon dots (CDs); microwave assisted synthesis method